Family-Based Education for Prevention and Management of Injuries in Vulnerable Populations - Triyanto, Arifin; Wati, Suis Galischa; Maf'ula, Dluha; Partini, Partini; Umami, Anisah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Injuries contribute to disability and morbidity in countries around the world. Among the elderly, falls are the most common type of injury, with an incidence rate of approximately 2.3–7% per 1,000 individuals. Injuries can lead to physical impairments, including reduced limb function. In the elderly population, particularly those aged 65 years and older, injuries are associated with a high risk of mortality and severe disability. Preventing injuries and falls is a critical public health concern. Families serve as essential support systems for addressing injuryrelated issues within households and the surrounding environment. This activity aimed to provide families with education on preventing and managing injuries in vulnerable populations. Health education sessions were delivered to health cadres and community members through lectures, discussions, and expert-led questionand-answer sessions. Educational materials included PowerPoint presentations and pocketbooks. At the conclusion of the sessions, a group demonstration was conducted on the management of splints in community settings. Knowledge was assessed using a questionnaire developed based on the health education materials. Fall risk screening was conducted using the First Time Injury Falls (FIF) instrument. The results revealed that among the 27 respondents, knowledge levels significantly improved after the educational sessions (p-value < 0.05). Fall risk screening outcomes indicated that 20 respondents (74.1%) were at low risk for falls, 5 respondents (18.5%) were at moderate risk, and 2 respondents (7.4%) were at high risk. Based on these findings, it can be concluded that health education is effective in enhancing family knowledge about injury prevention and management in vulnerable populations.